Multifunctional coatings combining bioactive peptides and affinity-based cytokine delivery for enhanced integration of degradable vascular grafts. (30th January 2020) - Clauder, Franziska; Zitzmann, Franziska D.; Friebe, Sabrina; Mayr, Stefan G.; Robitzki, Andrea A.; Beck-Sickinger, Annette G.
Abstract : Mussel-derived surface coatings present integrin- and heparin-binding peptides for cell adhesion and modulator protein delivery to improve the endothelialization of biodegradable cardiovascular implants. Abstract : Insufficient endothelialization of cardiovascular devices is a high-risk factor for implant failure. Presentation of extracellular matrix (ECM)-derived coatings is a well-known strategy to improve implant integration. However, the complexity of the system is challenging and strategies for applying multifunctionality are required. Here, we engineered mussel-derived surface-binding peptides equipped with integrin (c[RGDfK]) and proteoglycan binding sites (FHRRIKA) for enhanced endothelialization. Surface-binding properties of the platform containing l -3, 4-dihydroxyphenylalanine (DOPA) residues were confirmed for hydrophilized polycaprolactone- co -lactide scaffolds as well as for glass and polystyrene. Further, heparin and the heparin-binding angiogenic factors VEGF, FGF-2 and CXCL12 were immobilized onto the peptide in a modular assembly. Presentation of bioactive peptides greatly enhanced human umbilical vein endothelial cell (HUVEC) adhesion and survival under static and fluidic conditions. In subsequent investigations, peptide-heparin-complexes loaded with CXCL12 or VEGF had an additional increasing effect on cell viability, differentiation and migration. Finally, hemocompatibility of the coatings was ensured. This study demonstrates that coatings combining adhesion peptides, glycosaminoglycans and modulators are a versatile tool to convey ECM-inspired multifunctionality to biomaterials and efficiently promote their integration.